How Governance Tools Facilitate Citizen Co-Production Behavior in Urban Community Micro-Regeneration: Evidence from Shanghai - Jinpeng Wu; Jing Xiong (Land, 2022)
Citizen participation and input in urban community micro-regeneration is a co-production behavior that is conducive to improving citizens’ sense of belonging, thereby promoting community governance. In the context of low co-production levels amongst citizens, how the government adopts mobilization instruments is an important challenge. This paper investigates whether governance tools can facilitate citizen co-production behavior in an urban community micro-regeneration setting using a structural equation modeling method and the stimulus organism response theory. Based on a survey of citizens who participated in community micro-regeneration co-production in Shanghai, this paper demonstrates the significant positive effects associated with information- and incentive-based tools in citizen in-role and extra-role co-production behavior; however, the effect degree was shown to differ. Moreover, the level of perceived benefits is a significant mediating variable between governance tools and in-role co-production behavior. In this study, we constructed and verified a novel and valuable theoretical perspective with which to explore urban regeneration. It was concluded that policymakers should follow the governance principle of classified development and tool matching for citizen co-production behavior in urban community micro-regeneration.